Evaluation Report on Western Ghats Development Programme (1980-82) - Planning Commission (Planning Commission, 1982)
The Secretaries Committee headed by Member, Planning Commission, at its meeting held on August 5, 1980, requested Programme Evaluation Organisation of the Planning Commission to conduct an evaluation study of the Western Ghats Development Programme (WGDP). In pursuance of this request, the evaluation study was undertaken in the States of Karnataka. Kerala, Maharashtra, Tamil Nadu and the Union Territory of Goa, Daman & Diu It was restricted to four important sectoral schemes which included minor irrigation, soil conservation, road works and forestry. Besides, a few case studies were also taken up for detailed investigation. The field investigation was initiated in January, 1981 and completed in August, 1981.
Programme Evaluation Organisation Planning Commission Government of India